Reception of antique and biblical images in R. M.Rilke’s collections «New poems» and «New poems second part» in the context of conception of dialogue of cultures - Syanava, Nastassia E. (Journal of the Belarusian State University. Philology, 2023)
The purpose of the work is to identify the characteristic features of the literary embodiment of the dialogue between ancient and biblical cultures in the collections of the Austrian poet R. M. Rilke «New poems» and «New poems second part» based on the reception of ancient and biblical images and motifs in these lyrical works. In the spirit of the aesthetics according to Buber and Bakhtin, poetic images and motifs are considered in the context of the concept of the dialogue of cultures at different levels of R. M. Rilke’s poetics. The interweaving of the biblical and ancient worlds in the collections not only illustrates the diversity of the world and the possibility of seeing in each object and image a special thing in itself through a new poetic form poem-object, but also embodies the poet’s approach to each object (animate and inanimate), phenomenon, state or feeling as a specific subject of the dialogue.